Waste Management Problems on Bawean Island, Indonesia - Hasanul Bulqiyah (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2023)
The policy on waste management in Gresik Regency is not implemented in Bawean Island, which is part of the Gresik Regency area. The absence of Temporary Processing Sites (TPS) and Final Processing Sites (TPA) has made the waste problem more widespread which has an impact on people's lives on Bawean Island. The purpose of this research is to find out the problems in waste management on Bawean Island. Qualitative research methods were used to explore the problems of waste management policy on Bawean Island through interviews, observation, and also documentation at the Gresik Regency Environmental Service and Community Leaders on Bawean Island by selecting subjects using purposive sampling. The results of the study found that the non-implementation of policies regarding waste management in Gresik Regency on Bawean Island was due to budget being the main problem for implementing waste management policies on Bawean Island. Then the government's lack of readiness in managing waste on Bawean Island, such as the lack of a Detailed Engineering Design (DED) concept, facilities and infrastructure in waste management, and outreach to the people of Bawean Island.